Gambaran pengetahuan ıbu menyusuı terhadap pıjat oksıtosın dı puskesmas Karang Rejo kota Tarakan - Sriargianti amir argi; Asmira Asmira; Muhammad Aris; Isnina Isnina (Journal Borneo, 2022)
Production of breast milk can be disrupted by the influence of less than the optimal formation of the hormone oxytocin. Oxytocin massage is a massage action in overcoming the problem of substandard milk production. Oxytocin massage can be done on the spine to the fifth-sixth vertebrae and is a way to increase the production of the hormones prolactin and oxytocin after childbirth which aims to increase the work of the parasympathetic nerves in stimulating the posterior pituitary. The purpose of this study was to describe the knowledge of breastfeeding mothers about oxytocin massage. This study used a descriptive method, sampling using non-probability sampling using accidental sampling technique with a total of 40 samples according to the inclusion and exclusion criteria, and collecting data using a knowledge questionnaire about oxytocin massage. Based on the results of the study, data were obtained in the form of a good level of knowledge (65.0%), sufficient (15.0%), and less (20.0%). The conclusion of this study shows that most breastfeeding mothers at the Karang Rejo Health Center in Tarakan City have good knowledge regarding oxytocin massage.